Економічна сутність трансакційних витрат виробничої діяльності - Яцина, Вікторія Валентинівна (НТУ "ХПІ", 2014)
У статті розглянуто сутність та природу виникнення трансакційних витрат, наведено підходи, що пояснюють природу їх походження. Проаналізовано трактування поняття трансакційних витрат, що були розроблені в рамках неоінституційної теорії. Розкрито сутнісне значення категорії трансакційні витрати виробничої діяльності та запропоноване власне визначення цього поняття. Обґрунтовано необхідність оптимізації трансакційних витрат для підвищення ефективності господарської діяльності підприємства.

In the article the essence and nature of transaction costs existence at the economic activitiesof enterprises have been considered, the approaches that explain the nature of their originare given. The transaction costs interpretations that have been developed within neoinstitutional theoryto establish the research distribution on the macro and micro levels have been analyzed. An important factor of the transaction costs appearance at the industrial goodsproduction isthe presence of the following characteristics: specificity of assets, the limited number of industrial goods producers and buyers, which causes the opportunistic behavior of contractors.Taking this factor into account the own definition of production activity transaction costs have been proposed.It is generalize results of existing definitions of transaction costs with specifying the conditions of their occurrence, and provides exact identification of the production activity transaction costs in the total aggregate costs. The necessity of transaction costs optimizingto increase the economic activity efficiency of industrial enterprises has been grounded.
The Economic Essence of the Production Activities Transaction Costs
Keywords: теорія трансакційних витрат; теорія вибору; теорія угод; ефективність підприємства; transaction cost theory; theory of choice; theory of agreements; production activity